Host and viral mechanisms of congenital Zika syndrome. Issue 1 (1st January 2019) - Liang, Brooke; Guida, José Paulo; Costa, Maria Laura; Mysorekar, Indira U.
ABSTRACT: In 2015–2016, in the Americas, and especially in northeast Brazil, a significant number of cases of microcephaly and other congenital brain abnormalities were linked with an outbreak of Zika virus (ZIKV) infection in pregnant women. While maternal symptoms of ZIKV are generally mild and self-limiting, clinical presentation in fetuses and newborns infected is extensive and includes microcephaly, decreased cortical development, atrophy and hypoplasia of the cerebellum and cerebellar vermis, arthrogryposis, and polyhydramnios. The term congenital ZIKV syndrome (CZS) was introduced to describe the range of findings associated with maternal-fetal ZIKV transmission. ZIKV is primarily transmitted by Aedes aegypti mosquitoes, however non-vector-dependent routes are also possible. Mechanisms of maternal-fetal transmission remain unknown, and the trans-placental route has been extensively studied in animal models and in human samples. The aim of this review was to summarize recent studies that helped to elucidate the mechanism of CZS in animal models and observational studies. There are still challenges in the diagnosis and prevention of CZS in humans, due to the large gap that remains in translating ZIKV research to clinical practice. Translational research linking governments, local health workers, scientists and industry is fundamental to improve care for mothers and children.